The Socio – Cultural Factors Related With Soccess of Productive Cooperatives in Yazd - akbar zare shahabadi; masoud hajizadehmeymandi; hamed sayarkhalaj (توسعه اجتماعی)
Driving force of economic growth and prosperity of any nation and the country.Cooperative sector is one of the three main sectors of our economy, according to Principle 44 of the constitution. The overall objective of this project is to study the factors affecting the success of the productive cooperatives of Yazd. Method: The study of application and survey methods. The study population include all members of active productive cooperatives in Yazd, where 196 of them were determined using Cochran's formula as the sample size. Data collected in this survey Investigated questionaire is used. Validity and reliability of the face and was confirmed using Cronbach's alpha. Results: The results showed that OG production cooperatives city of Yazd have successfully are above middle. The positive and significant relationship between education, participation, learning and cultural capital with success of productive cooperatives. Multivariable regression analysis revealed that participation variables, education, training and cultural capital in total 39% of the variation can explain the success of productive cooperatives. Success of productive cooperatives assess their dependent on several factors requires a multifaceted approach.